Case Report: The first report of PPP2R1A mutations in mesonephric-like adenocarcinoma of endometrial carcinoma - Cai, Lei; Yang, Chenmin; Gu, Yijin; Dong, Lei; Feng, Weiwei (Frontiers in Oncology, 2023)
We performed clinical treatment, histopathology, immunohistochemistry and molecular analyses.To compare with the published literature and have a reference overview.A 57-year-old woman and a 77-year-old woman presented with mesonephric-like adenocarcinoma of endometrium at an early clinical stage. The former had no deep myometrial infiltration and no regional lymph node involvement. The latter had deep myometrial infiltration , presence of LVSI and no regional lymph node involvement. Both of the tumor cells were positive for PAX8, GATA-3,CD-10,TTF-1,AE1/AEs,Ki67,P53 and P16 in immunohistochemical staining (IHC)Test. Primary tumors were examined for gene mutations by next generation sequencing.The former was identified KRAS mutation. The latter had KRAS,PIKCA and PPP2R1A mutations.To our knowledge, it is the first time that PPP2R1A(protein phosphatase 2,regulatory subunit A,α) mutation in MLA is reported in English literature.